2013
DOI: 10.4067/s0717-95022013000200065
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Response in Offspring Male Rats Exposed to Prenatal Stress and to Early Postnatal Stimulation

Abstract: Stress in pregnant rats alters the pattern of secretion of corticosterone (COR) and modifies transplacentally hypothalamic-pituitary-adrenal axis (HPA) fetus. Prenatal stress during the critical hypothalamic differentiation is related to decreased fertility of male offspring by an increase in the basal level of COR. This modification could induce long-term changes in the process of apoptosis in the testis. However, early postnatal handling increases maternal behavior and could reverse the effects caused by inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 73 publications
(71 reference statements)
3
19
0
Order By: Relevance
“…Late effects of various forms of stress were studied by numerous authors [22] stated that water deprivation in pregnant rats increased number of TUNEL positive cells and germ cell apoptosis of the offsprings when reached puberty [9] found that immobilization stress to pregnant rats resulted in increased apoptotic cells of the offsprings at adulthood. The authors hypothesized that the increase in testicular apoptosis was the result of decline of gonadotropins and subsequently testosterone hormonal level that influenced the testicular cellular viability [37] Citation: Lasheen SS, Refaat SH, EI-Nefiawy NE, Abd-Elgawad RA, Othman AI, et al found that testosterone replacement at birth in offspring males exposed to prenatal stress was able to reverse changes in sexual behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Late effects of various forms of stress were studied by numerous authors [22] stated that water deprivation in pregnant rats increased number of TUNEL positive cells and germ cell apoptosis of the offsprings when reached puberty [9] found that immobilization stress to pregnant rats resulted in increased apoptotic cells of the offsprings at adulthood. The authors hypothesized that the increase in testicular apoptosis was the result of decline of gonadotropins and subsequently testosterone hormonal level that influenced the testicular cellular viability [37] Citation: Lasheen SS, Refaat SH, EI-Nefiawy NE, Abd-Elgawad RA, Othman AI, et al found that testosterone replacement at birth in offspring males exposed to prenatal stress was able to reverse changes in sexual behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Claims have been raised that noise stress exposure could have an adverse effect on male reproductive organs. Several studies reported structural and functional affection of testicular tissue due to noise stress exposure in adult males [5][6][7][8][9]. However, adverse effects of chronic noise stress exposure on the testis in prenatal or pre-pubertal periods are deficient.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Bebbere et al (2013) failed to detect differences in allelic expression ratios and IGF2R second intron DMR methylation in the few (n ¼ 4) overgrown IVP fetuses studied compared with normal weight IVP and in vivo conceived fetuses at Day 80 of gestation in the cow. Instead, Chen Cárdenas et al (2013) found a loss of imprinting leading to biallelic expression of KCNQ1OT1 (KCNQ1 oppositie strand/ antisense transcript 1, the gene most misregulated in BWS) in bovine LOS fetuses derived from IVP embryos, and that this is associated with a loss of methylation at the KvDMR1 (KCNQ1 differentially methylated region 1) on the maternal allele. This observation confirmed an earlier report of abnormal hypomethylation of KvDMR1 and expression of KCNQ1OT1 in two of seven SCNT cloned calves and one of two IVP-derived calves (Hori et al 2010).…”
Section: Epigenetic Programming Of Long-term Developmentmentioning
confidence: 99%
“…25 When immobilization stress is applied to pregnant rats, Mayer et al 26 observed that basal corticosterone and glucose levels were higher in prenatally stressed animals, in agreement with results reported by Vallée et al 27 A group of rats with immobilization stress showed a hyperactive hypothalamic-pituitary-gonadal axis, 15,28 alterations in plasmatic LH and testosterone plasmatic levels, testis with reduced weight and higher apoptosis caused by the prenatal stress. 29 In humans, exposure of the developing brain to various types of environmental stressors during intrauterine life increases the susceptibility to neuropsychiatric disorders such as autism, attention deficit, hyperactivity disorder and schizophrenia. 30 In the same way, likelihood of developing anxiety, depression and learning deficits that are associated with structural alterations in the offspring hippocampus were observed in animals exposed to prenatal stress.…”
Section: Effect Of Prenatal Stress On Hypothalamicpituitary-adrenocormentioning
confidence: 99%
“…Specific experimental manipulations of the rat postnatal environment have been shown to exert robust and marked effects on neurobiological, physiological and behavioral phenotypes in adulthood. 57 For example, Chen et al 29 demonstrated that postnatal PS returned the levels of LH and testosterone to normal values and reduced apoptotic index observed in male testes from prenatal stressed animals.…”
Section: Effect Of Postnatal Early Stimulations On Hypothalamic-pituimentioning
confidence: 99%